2011
DOI: 10.1373/clinchem.2010.158220
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Study of 3 Direct-to-Consumer Genetic-Testing Services

Abstract: BACKGROUND:Several companies offer direct-toconsumer (DTC) genetic testing to evaluate ancestry and wellness. Massive-scale testing of thousands of single-nucleotide polymorphisms (SNPs) is not error free, and such errors could translate into misclassification of risk and produce a false sense of security or unnecessary anxiety in an individual. We evaluated 3 DTC services and a genomics service that are based on DNA microarray or solution genotyping with hydrolysis probes (TaqMan analysis) and compared the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 8 publications
1
52
0
Order By: Relevance
“…Only rarely has there been a discussion of the data quality and its use for ancestry testing. Previous reports that compared genotyping results examined panels of very different sizes (13,14) so the comparison was necessarily limited in scope. While they found high concordance, there were too few SNPs compared to draw strong conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Only rarely has there been a discussion of the data quality and its use for ancestry testing. Previous reports that compared genotyping results examined panels of very different sizes (13,14) so the comparison was necessarily limited in scope. While they found high concordance, there were too few SNPs compared to draw strong conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Some case studies have reported DTC-GT results with apparent clinical utility [10][11][12] and other studies report results with no clinical utility. [13][14][15] The perceptions and attitudes of the general public towards DTC-GT have also been explored. Although a strong public interest in predictive genetic testing has been reported, [16][17][18][19] this is often accompanied by the desire for closer involvement of a medical professional.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some ethical and methodological concerns over the use of genetic testing to support personalized nutrition, 84,85 direct-to-consumer tests for genetic predisposition to a range of diseases are already available, 86 which suggests that similar tests might eventually be developed to identify polymorphisms associated with obesity. Advances in nutritional research and the development of 'omics' technologies have greatly improved our ability to identify new candidate genes and genetic variants putatively involved in gene-nutrient interactions.…”
mentioning
confidence: 99%